Preparation method of high-rate lithium manganese iron phosphate positive electrode material and lithium battery

By using lithium cobalt oxide and polyvinyl alcohol/chitosan on the positive electrode material of lithium manganese phosphate battery, the problems of high-rate charging and discharging performance and cycling performance of lithium manganese phosphate battery are solved, and the problem of lithium manganese phosphate battery in high-rate charging and discharging performance is achieved. The high rate performance and high specific capacity of the material are obtained.

CN118929618BActive Publication Date: 2025-02-14HUNAN YUNENG NEW ENERGY BATTERY MATERIALS CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411435131.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-15
Publication Date
2025-02-14
Estimated Expiration
2044-10-15

AI Technical Summary

Technical Problem

In practical applications, lithium manganese iron phosphate batteries face problems such as low electronic conductivity, slow one-dimensional diffusion rate of lithium ions and Jahn-teller effect, which affect their high-rate charging and discharging performance and cycle performance.

Method used

Lithium cobalt oxide is used as the main coating layer to coat lithium manganese iron phosphate, and a secondary coating layer is formed by polyvinyl alcohol/chitosan to form a carbon layer with uniform micro-holes, improving the conductivity of the material and lithium ion diffusion performance .

Benefits of technology

It improves the rate performance and cycle performance of lithium manganese iron phosphate material, has a high specific capacity, and enhances the battery's high-rate charging and discharging capabilities.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention discloses a preparation method of a high-rate lithium iron manganese phosphate positive electrode material and a lithium battery, belonging to the technical field of lithium batteries. A double coating layer is formed on the surface of the lithium iron manganese phosphate material by combining the two methods of in-situ coating of lithium cobalt oxide nanoparticles and polyvinyl alcohol / chitosan gel coating. The main coating layer of lithium cobalt oxide can supplement lithium elements to increase the specific capacity, and based on its layered structure, it can inhibit the growth of particles while facilitating the diffusion of lithium ions. Polyvinyl alcohol and chitosan are cross-linked on the surface of the material to form a gel coating to prevent particle agglomeration. Due to the cross-linking to form a network structure, the carbon layer formed by carbonization is continuous and uniform. Based on the action of the double coating layer, the lithium iron manganese phosphate positive electrode material has high-rate performance, high specific capacity and good cycle performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of lithium batteries, and in particular relates to a preparation method of a high-rate lithium manganese iron phosphate positive electrode material and a lithium battery. Background Art

[0002] Lithium iron phosphate and ternary materials are the two most commonly used materials in the field of power batteries. However, insufficient energy density has always been a pain point for lithium iron phosphate. The energy density of the positive electrode material directly affects the overall performance of the power battery, and the capacity and voltage together determine the energy density of the material.

[0003] Manganese itself has the characteristic of high voltage. After lithium iron is doped with manganese, the voltage platform can be increased from 3.4V to 3.8~4.1V, thereby increasing the theoretical energy density by 10%~20%. Lithium manganese iron phosphate batteries can provide electric vehicles with a longer range than lithium iron phosphate batteries. From the perspective of market demand, the rapid development of the new energy vehicle industry has promoted the advancement of lithium iron phosphate battery production technology.

[0004] However, lithium manganese iron phosphate still faces some challenges in practical applications, such as low electronic conductivity, slow one-dimensional diffusion rate of lithium ions and Jahn-Teller effect, which will affect the high-rate charge and discharge performance and cycle performance of lithium batteries. High-rate charge and discharge means that the battery can complete the charging or discharging process in a shorter time, which is of great significance for the promotion and application of new energy vehicles.

[0005] At present, the improvement technologies for improving the performance of lithium manganese iron phosphate materials mainly include nano-sizing, carbon coating and ion doping. Among them, surface carbon coating is the most common way of material modification. Although carbon coating can enhance the conductivity and prevent the dissolution of manganese ions, the introduction of inactive substances leads to a decrease in the specific capacity of the electrode. In addition, the uniformity and continuity of the carbon coating layer will affect the construction of the electron channel. At present, it is still challenging to form a uniform and continuous carbon coating layer on the surface of the material through a simple process. Summary of the invention

[0006] The object of the present invention is to provide a method for preparing a high-rate lithium iron manganese phosphate positive electrode material and a lithium battery. The lithium iron manganese phosphate positive electrode material prepared by the method has high-rate performance.

[0007] The purpose of the present invention can be achieved through the following technical solutions:

[0008] The present invention provides a method for preparing a high-rate lithium manganese iron phosphate positive electrode material, comprising the following steps:

[0009] S1, mixing a phosphorus source, a manganese source, an iron source and a lithium source, and ball milling them using ethanol as a medium;

[0010] S2, ball milling and spray drying to obtain a lithium manganese iron phosphate precursor;

[0011] S3, mixing the cobalt source and the lithium source and grinding them, and then grinding them after heat treatment to obtain nano-lithium cobalt oxide;

[0012] S4, mixing the lithium iron manganese phosphate precursor and nano-lithium cobalt oxide, ball-milling and then microwave drying to obtain LCO@LFMP precursor, wherein the nano-lithium cobalt oxide can adhere to the surface of the precursor particles due to the nano effect, and the layered lithium cobalt oxide forms a coating layer on the surface of the precursor;

[0013] S5, dissolving polyvinyl alcohol and chitosan in an acetic acid aqueous solution, adding LCO@LFMP precursor for ultrasonic dispersion and mixing, adding glutaraldehyde to form a gel coating after cooling, filtering, vacuum drying and pre-sintering in sequence to obtain a C-LCO@LFMP precursor, polyvinyl alcohol and chitosan are cross-linked under the action of glutaraldehyde to form an interpenetrating network hydrogel, forming a continuous and uniform coating layer on the surface of the LCO@LFMP precursor, and gradually carbonizing after sintering to form a carbon layer with uniform micropores;

[0014] S6. The C-LCO@LFMP precursor is calcined at high temperature and then crushed and sieved to obtain a positive electrode material.

[0015] Preferably, in step S1, the phosphorus source is phosphoric acid, the manganese source is manganese dioxide, the iron source is ferrous oxalate, and the lithium source is lithium oxalate, and the mixture is prepared according to Li: (Fe+Mn): P = 1:1:1, Fe:Mn = (2:8) to (4:6).

[0016] Preferably, in step S3, the cobalt source is cobalt tetroxide, and the lithium source is lithium carbonate, and the mixture is prepared according to Li:Co=1:1.

[0017] Preferably, the heat treatment temperature is 800° C. and the time is 10 h.

[0018] Preferably, in step S4, the mass ratio of the lithium manganese iron phosphate precursor to the nano-lithium cobalt oxide is 100:1-2.

[0019] Preferably, the microwave drying temperature is 300-400° C., and the microwave drying time is 45-60 min.

[0020] Preferably, in step S5, the vacuum drying temperature is 50-60° C., the vacuum drying time is 10 h to 12 h, the pre-sintering temperature is 200-300° C., and the pre-sintering time is 2 to 3 h.

[0021] Preferably, the mass fraction of acetic acid in the acetic acid aqueous solution is 5%, the mass ratio of polyvinyl alcohol to chitosan is 3-5:1, the concentration of polyvinyl alcohol and chitosan dissolved in the acetic acid aqueous solution is 0.05 g / mL, the amount of LCO@LFMP precursor added is 5.0-5.8 g / mL, and the amount of glutaraldehyde added is 0.1 mol / L. As a carbon source, the gel coating layer formed by polyvinyl alcohol and chitosan should not be too thick. Too much addition of LCO@LFMP precursor will cause incomplete coating. When too little addition of LCO@LFMP precursor, the coating layer is thick, which is not conducive to lithium ion diffusion.

[0022] Preferably, the high temperature calcination temperature is 600-750° C., and the calcination time is 12-24 hours.

[0023] The present invention also provides a lithium battery, wherein the positive electrode material of the lithium battery is prepared by the above-mentioned preparation method.

[0024] Beneficial effects of the present invention:

[0025] (1) Compared with direct carbon coating, lithium iron manganese phosphate is coated with lithium cobalt oxide as the main coating layer. While supplementing lithium ions, lithium cobalt oxide, as a layered crystal structure, is conducive to the diffusion of lithium ions, inhibits the increase of lithium iron manganese phosphate particles during high-temperature calcination, shortens the ion diffusion distance, improves the rate performance of lithium iron manganese phosphate materials, and has a higher specific capacity.

[0026] (2) Polyvinyl alcohol / chitosan is used as the carbon source to form a secondary coating layer. Polyvinyl alcohol and chitosan are cross-linked under the action of glutaraldehyde to form a gel. After the gel is sintered, a continuous and uniform carbon coating layer can be formed on the surface of the particles to prevent material agglomeration. The thickness of the coating layer is adjusted by controlling the ratio of the coating layer and the precursor, thereby improving the conductivity of the positive electrode material while inhibiting the interfacial side reactions and ensuring good cycle performance. DETAILED DESCRIPTION

[0027] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0028] Example 1

[0029] This embodiment provides a method for preparing a high-rate lithium manganese iron phosphate positive electrode material, comprising the following steps:

[0030] S1. Phosphoric acid, manganese dioxide, ferrous oxalate and lithium oxalate are mixed according to the ratio of Li: (Fe + Mn): P = 1: 1: 1, Fe: Mn = 2: 8, and ball milled with ethanol as the medium;

[0031] S2, after ball milling, spray drying at 330° C. to obtain a lithium manganese iron phosphate precursor;

[0032] S3, mixing cobalt tetroxide and lithium carbonate according to Li:Co=1:1, ball milling, heat treating at 800°C for 10h, mixing with isopropanol to form a slurry with a solid content of 70%, putting into a pin-type nano sand mill for grinding, using zirconium oxide grinding beads with a particle size of 0.2mm and a filling rate of 80%, drying after grinding to remove isopropanol to obtain nano-lithium cobalt oxide with a particle size of 100-200nm;

[0033] S4, mixing the lithium iron manganese phosphate precursor and nano-lithium cobalt oxide in a mass ratio of 100:1, ball-milling with ethanol as a medium, and then microwave drying at 300°C for 1h to obtain the LCO@LFMP precursor;

[0034] S5. Dissolve polyvinyl alcohol and chitosan in an acetic acid aqueous solution with a mass ratio of 3:1, and the concentration of polyvinyl alcohol and chitosan in the acetic acid aqueous solution is 0.05 g / mL; add LCO@LFMP precursor in an amount of 5 g / mL, and add glutaraldehyde in an amount of 0.1 mol / L after ultrasonic dispersion and mixing to form a gel coating on the surface of LCO@LFMP precursor. The filtered solid is vacuum dried at 50°C in a vacuum drying oven for 12 h, and pre-sintered at 300°C in a nitrogen atmosphere in a tubular furnace for 2 h to obtain C-LCO@LFMP precursor;

[0035] S6. The C-LCO@LFMP precursor was calcined at 750°C for 12 h, and then crushed and sieved to obtain the positive electrode material.

[0036] The prepared positive electrode material was used as the positive electrode raw material and the lithium sheet was used as the negative electrode to assemble a lithium manganese iron phosphate button half-cell for electrochemical performance testing.

[0037] Example 2

[0038] The difference from Example 1 is that the mass ratio of the lithium manganese iron phosphate precursor to the nano-lithium cobalt oxide is 100:1.5, and the other steps are the same as Example 1.

[0039] Example 3

[0040] The difference from Example 1 is that the mass ratio of the lithium manganese iron phosphate precursor to the nano-lithium cobalt oxide is 100:2, and the other steps are the same as Example 1.

[0041] Example 4

[0042] The difference from Example 1 is that the amount of LCO@LFMP precursor added in step S5 is 5.4 g / mL, and the other steps are the same as Example 1.

[0043] Example 5

[0044] The difference from Example 1 is that the amount of LCO@LFMP precursor added in step S5 is 5.8 g / mL, and the other steps are the same as Example 1.

[0045] Example 6

[0046] The difference from Example 1 is that in step S5, the mass ratio of polyvinyl alcohol to chitosan is 4:1, and the other steps are the same as Example 1.

[0047] Example 7

[0048] The difference from Example 1 is that in step S5, the mass ratio of polyvinyl alcohol to chitosan is 5:1, and the other steps are the same as Example 1.

[0049] Example 8

[0050] This embodiment provides a method for preparing a high-rate lithium manganese iron phosphate positive electrode material, comprising the following steps:

[0051] S1. Phosphoric acid, manganese dioxide, ferrous oxalate and lithium oxalate are mixed according to the ratio of Li: (Fe + Mn): P = 1:1:1, Fe: Mn = 4:6, and ball milled with ethanol as the medium;

[0052] S2, after ball milling, spray drying at 330° C. to obtain a lithium manganese iron phosphate precursor;

[0053] S3, mixing cobalt tetroxide and lithium carbonate according to Li:Co=1:1, ball milling, heat treating at 800°C for 10h, mixing with isopropanol to form a slurry with a solid content of 70%, putting into a pin-type nano sand mill for grinding, using zirconium oxide grinding beads with a particle size of 0.2mm and a filling rate of 80%, drying after grinding to remove isopropanol to obtain nano-lithium cobalt oxide with a particle size of 100-200nm;

[0054] S4, mixing the lithium iron manganese phosphate precursor and nano-lithium cobalt oxide in a mass ratio of 100:1.5, ball-milling with ethanol as a medium, and then microwave drying at 400°C for 45 minutes to obtain the LCO@LFMP precursor;

[0055] S5. Dissolve polyvinyl alcohol and chitosan in an acetic acid aqueous solution with a mass ratio of 4:1, and the concentration of polyvinyl alcohol and chitosan in the acetic acid aqueous solution is 0.05 g / mL; add LCO@LFMP precursor in an amount of 5.4 g / mL, and add glutaraldehyde in an amount of 0.1 mol / L after ultrasonic dispersion and mixing to form a gel coating on the surface of LCO@LFMP precursor. The filtered solid is vacuum dried at 60°C in a vacuum drying oven for 10 h, and pre-sintered at 200°C in a nitrogen atmosphere in a tubular furnace for 3 h to obtain C-LCO@LFMP precursor;

[0056] S6. The C-LCO@LFMP precursor was calcined at 600°C for 24 hours and then crushed and sieved to obtain the positive electrode material.

[0057] The prepared positive electrode material was used as the positive electrode raw material and the lithium sheet was used as the negative electrode to assemble a lithium manganese iron phosphate button half-cell for electrochemical performance testing.

[0058] Example 9

[0059] This embodiment provides a method for preparing a high-rate lithium manganese iron phosphate positive electrode material, comprising the following steps:

[0060] S1. Phosphoric acid, manganese dioxide, ferrous oxalate and lithium oxalate are mixed according to the ratio of Li: (Fe + Mn): P = 1:1:1, Fe: Mn = 3:7, and ball milled with ethanol as the medium;

[0061] S2, after ball milling, spray drying at 330° C. to obtain a lithium manganese iron phosphate precursor;

[0062] S3, mixing cobalt tetroxide and lithium carbonate according to Li:Co=1:1, ball milling, heat treating at 800°C for 10h, mixing with isopropanol to form a slurry with a solid content of 70%, putting into a pin-type nano sand mill for grinding, using zirconium oxide grinding beads with a particle size of 0.2mm and a filling rate of 80%, drying after grinding to remove isopropanol to obtain nano-lithium cobalt oxide with a particle size of 100-200nm;

[0063] S4, mixing the lithium iron manganese phosphate precursor and nano-lithium cobalt oxide in a mass ratio of 100:1.5, ball milling with ethanol as a medium, and then microwave drying at 350°C for 50 min to obtain the LCO@LFMP precursor;

[0064] S5. Dissolve polyvinyl alcohol and chitosan in an acetic acid aqueous solution with a mass ratio of 4:1, and the concentration of polyvinyl alcohol and chitosan in the acetic acid aqueous solution is 0.05 g / mL; add LCO@LFMP precursor in an amount of 5.4 g / mL, and add glutaraldehyde in an amount of 0.1 mol / L after ultrasonic dispersion and mixing to form a gel coating on the surface of LCO@LFMP precursor. The filtered solid is vacuum dried at 60°C in a vacuum drying oven for 10 h, and pre-sintered at 250°C in a nitrogen atmosphere in a tubular furnace for 2.5 h to obtain C-LCO@LFMP precursor;

[0065] S6. The C-LCO@LFMP precursor was calcined at 650°C for 16 h and then crushed and sieved to obtain the positive electrode material.

[0066] The prepared positive electrode material was used as the positive electrode raw material and the lithium sheet was used as the negative electrode to assemble a lithium manganese iron phosphate button half-cell for electrochemical performance testing.

[0067] Comparative Example 1

[0068] Compared with Example 1, the positive electrode material coating layer of this comparative example is not coated with lithium cobalt oxide material, and the specific steps are as follows:

[0069] S1. Phosphoric acid, manganese dioxide, ferrous oxalate and lithium oxalate are mixed according to the ratio of Li: (Fe + Mn): P = 1: 1: 1, Fe: Mn = 2: 8, and ball milled with ethanol as the medium;

[0070] S2, after ball milling, spray drying at 330° C. to obtain a lithium manganese iron phosphate precursor;

[0071] S3, polyvinyl alcohol and chitosan were dissolved in an acetic acid aqueous solution with a mass ratio of 3:1, and the concentration of polyvinyl alcohol and chitosan in the acetic acid aqueous solution was 0.05g / mL; lithium iron manganese phosphate precursor was added in an amount of 5g / mL, and glutaraldehyde was added in an amount of 0.1mol / L after ultrasonic dispersion and mixing, and a gel coating was formed on the surface of the lithium iron manganese phosphate precursor. The filtered solid was vacuum dried at 50°C in a vacuum drying oven for 12h, and pre-sintered at 300°C in a tubular furnace under a nitrogen atmosphere for 2h to obtain a C@LFMP precursor;

[0072] S4. The C@LFMP precursor was calcined at 750°C for 12 h, and then crushed and sieved to obtain the positive electrode material.

[0073] The prepared positive electrode material was used as the positive electrode raw material and the lithium sheet was used as the negative electrode to assemble a lithium manganese iron phosphate button half-cell for electrochemical performance testing.

[0074] Comparative Example 2

[0075] Compared with Example 1, the positive electrode material coating layer of this comparative example does not have a polyvinyl alcohol / chitosan material carbon coating, and the specific steps are as follows:

[0076] S1. Phosphoric acid, manganese dioxide, ferrous oxalate and lithium oxalate are mixed according to the ratio of Li: (Fe + Mn): P = 1: 1: 1, Fe: Mn = 2: 8, and ball milled with ethanol as the medium;

[0077] S2, after ball milling, spray drying at 330° C. to obtain a lithium manganese iron phosphate precursor;

[0078] S3, mixing cobalt tetroxide and lithium carbonate according to Li: Co = 1: 1, ball milling, heat treating at 800 ° C for 10 hours, grinding, mixing with isopropanol to form a slurry with a solid content of 70%, putting it into a pin-type nano sand mill for grinding, grinding with zirconium oxide grinding beads with a particle size of 0.2 mm and a filling rate of 80%, drying after grinding to remove isopropanol to obtain nano-lithium cobalt oxide with a particle size of 100-200 nm;

[0079] S4, mixing the lithium iron manganese phosphate precursor and nano-lithium cobalt oxide in a mass ratio of 100:1, ball-milling with ethanol as a medium, and then microwave drying at 300°C for 1h to obtain the LCO@LFMP precursor;

[0080] S5. The LCO@LFMP precursor is calcined at 750°C for 12 h, and then crushed and sieved to obtain a positive electrode material.

[0081] The prepared positive electrode material was used as the positive electrode raw material and the lithium sheet was used as the negative electrode to assemble a lithium manganese iron phosphate button half-cell for electrochemical performance testing.

[0082] Comparative Example 3

[0083] Compared with Example 1, the positive electrode material of this comparative example has no coating layer, and the specific steps are as follows:

[0084] S1. Phosphoric acid, manganese dioxide, ferrous oxalate and lithium oxalate are mixed according to the ratio of Li: (Fe + Mn): P = 1: 1: 1, Fe: Mn = 2: 8, and ball milled with ethanol as the medium;

[0085] S2, after ball milling, spray drying at 330° C. to obtain a lithium manganese iron phosphate precursor;

[0086] S3. The lithium manganese iron phosphate precursor is calcined at 750° C. for 12 h, and then crushed and sieved to obtain a positive electrode material.

[0087] The prepared positive electrode material was used as the positive electrode raw material and the lithium sheet was used as the negative electrode to assemble a lithium manganese iron phosphate button half-cell for electrochemical performance testing.

[0088] The performance tests were performed on the lithium iron manganese phosphate positive electrode materials and lithium iron manganese phosphate button half-cells prepared in Examples 1 to 9 and Comparative Examples 1 to 3. The results are shown in Table 1.

[0089]

[0090] As can be seen from Table 1, the positive electrode material prepared by the embodiment of the present invention has high rate performance. In Examples 1-3, the appropriate increase in the mass proportion of lithium cobalt oxide as a coating layer will increase the specific capacity of the material, but too much increase will cause the coating layer to be too thick, increase the lithium ion migration distance, and reduce the rate performance; Example 4 and Example 5 are based on Example 1 to adjust the mass ratio of the precursor and the polyvinyl alcohol / chitosan coating layer, the precursor mass is increased, the coating thickness is reduced, the conductivity is reduced, but the ion migration distance is shortened, wherein the ratio in Example 4 is the best, and the rate performance and cycle performance are the best; In Example 6 and Example 7, the proportion of polyvinyl alcohol increases, the cross-linking degree increases, and the gel structure is more compact. The rate performance of Example 6 is significantly improved compared with Example 1, but in Example 7, due to excessive cross-linking, the gel hardness increases, which is not conducive to uniform coating on the particle surface. At this time, the performance of the prepared positive electrode material is reduced compared with Example 6; Example 8 and Example 9 are to adjust the iron-manganese ratio in the material, and appropriately adjusting the ratio is conducive to improving the electrochemical performance of the material. Combining the test results of Comparative Examples 1-3 and Example 1, the double-layer coated lithium manganese iron phosphate positive electrode material prepared in Example 1 has more excellent rate performance and cycle performance, and higher specific capacity.

[0091] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.

[0092] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A method for preparing a high-rate lithium manganese iron phosphate positive electrode material, characterized in that: The following steps are involved: S1, mixing a phosphorus source, a manganese source, an iron source and a lithium source, and ball milling them using ethanol as a medium; S2, ball milling and spray drying to obtain a lithium manganese iron phosphate precursor; S3, mixing the cobalt source and the lithium source and grinding them, and then grinding them after heat treatment to obtain nano-lithium cobalt oxide; S4, mixing the lithium iron manganese phosphate precursor and the nano-lithium cobalt oxide, ball-milling the mixture, and then microwave drying the mixture to obtain the LCO@LFMP precursor; S5, dissolving polyvinyl alcohol and chitosan in an acetic acid aqueous solution, adding LCO@LFMP precursor for ultrasonic dispersion and mixing, adding glutaraldehyde to form a gel coating after cooling, and filtering, vacuum drying and pre-sintering in sequence to obtain a C-LCO@LFMP precursor; S6, calcining the C-LCO@LFMP precursor at high temperature, crushing and screening to obtain a positive electrode material; In step S1, the phosphorus source is phosphoric acid, the manganese source is manganese dioxide, the iron source is ferrous oxalate, and the lithium source is lithium oxalate, and the mixture is prepared according to Li: (Fe+Mn): P = 1:1:1, Fe: Mn = (2:8) to (4:6); In step S3, the cobalt source is cobalt tetroxide, and the lithium source is lithium carbonate, which are mixed according to Li:Co=1:1; The mass fraction of acetic acid in the acetic acid aqueous solution is 5%, the mass ratio of polyvinyl alcohol to chitosan is 3-5:1, the concentration of polyvinyl alcohol and chitosan dissolved in the acetic acid aqueous solution is 0.05 g / mL, the amount of LCO@LFMP precursor added is 5.0-5.8 g / mL, and the amount of glutaraldehyde added is 0.1 mol / L.

2. The method for preparing a high-rate lithium iron manganese phosphate positive electrode material according to claim 1, characterized in that: The heat treatment temperature is 800° C. and the time is 10 hours.

3. The method for preparing a high-rate lithium manganese iron phosphate positive electrode material according to claim 1, characterized in that: In step S4, the mass ratio of the lithium manganese iron phosphate precursor to the nano-lithium cobalt oxide is 100:1-2.

4. The method for preparing a high-rate lithium manganese iron phosphate positive electrode material according to claim 1, characterized in that: The microwave drying temperature is 300-400° C., and the microwave drying time is 45-60 minutes.

5. The method for preparing a high-rate lithium manganese iron phosphate positive electrode material according to claim 1, characterized in that: In step S5, the vacuum drying temperature is 50-60°C, the vacuum drying time is 10h-12h, the pre-sintering temperature is 200-300°C, and the pre-sintering time is 2-3h.

6. The method for preparing a high-rate lithium iron manganese phosphate positive electrode material according to claim 1, characterized in that: The high temperature calcination temperature is 600-750° C., and the calcination time is 12-24 hours.

7. A lithium battery, characterized in that: The positive electrode material of the lithium battery is prepared by the preparation method according to any one of claims 1 to 6.

Citation Information

Patent Citations

  • LiFePO4 anode material for chitosan-modified lithium ion battery

    CN101465425A

  • Hydrothermal synthesis method for lithium ferromanganese phosphate anode material of lithium ion battery

    CN102249208A

  • Lithium cobaltate-coated high-nickel ternary positive electrode material and preparation method thereof

    CN110247031A